Perception of Complementary Medicine and Treatment Adherence as Predictors of Self-Efficacy in Individuals with Chronic Conditions in Mexico - Karina Isabel Casco-Gallardo; Nissa Yaing Torres-Soto; Claudia Nelly Orozco-González; Nancy Griselda Pérez-Briones; José Antonio Guerrero-Solano; Gabriela Maldonado-Muñiz; Claudia Atala Trejo-García; Benjamín López-Nolasco (MDPI AG, 2024)
Chronic diseases such as type 2 diabetes mellitus (T2DM), arterial hypertension (HTN), and obesity are significant global health challenges, contributing to millions of premature deaths. In Mexico, these pose major challenges due to limited access to healthcare and inadequate primary care quality. Complementary medicine presents itself as an adjuvant in this context, offering minimally invasive techniques to enhance physical, mental, and spiritual well-being. However, effective treatment adherence is crucial for positive outcomes, influenced by self-efficacy, resulting in persistently low adherence rates-a pressing public health concern. This observational study aimed to explore how perceptions of complementary medicine and treatment adherence predict self-efficacy among individuals with chronic diseases in Mexico. Data were collected from 113 participants with chronic conditions, including T2DM, HTN, and obesity. Participants completed surveys assessing perception of complementary medicine, treatment adherence, and self-efficacy. Statistical analyses, including correlations and regression, were conducted to examine the relationships between variables. The study revealed significant correlations between the perception of complementary medicine, treatment adherence, and self-efficacy. Treatment adherence was positively associated with self-efficacy, while perception of holistic medicine was negatively correlated with self-efficacy. Perception of complementary medicine and adherence to treatment were found to predict 41.9% (p = 0.001) self-efficacy. These findings underscore the potential of complementary therapies in enhancing self-efficacy levels, and highlight the importance of holistic healthcare approaches in managing chronic conditions. Further research is needed to better understand these relationships and their implications for healthcare outcomes in Mexico and beyond.